Efetividade da atenção farmacêutica aplicada a pacientes idosos ambulatoriais em uso de anticoagulante oral com história de fibrilação atrial em hospital público - Costa, Márcia Gisele Santos da (2008)
The chronic anticoagulation in patients aged over 65 with atrial fibrillation (AF), translates into more concern to the clinic because of the risk of bleeding including brain, beyond the need for periodic controls, without showing a satisfactory response anticoagulant therapy. This study aimed to evaluate the effectiveness of the free supply of oral anticoagulants anticoagulation clinic in a public hospital, through the participation of the pharmacist for dispensing design the profile of these patients with a view to submitting a proposal to accompany with pharmacotherapeutic view to optimizing the treatment and maintenance of patients with the INR (International Normalized Ratio) within the target. Was evaluated in a Randomized Clinical Trial, 62 patients divided into 2 groups (intervention and control) with 31 members each. We applied a methodology to guide the pharmacological treatment, using so-called pharmaceutical care, where the act of dispensing is done consciously at the time of delivery, with systematic monitoring, aiming at a rationalp pharmacotherapy and result-defined and measurable , focused on the quality of life of the patient. Results: 29% of the control group and 36% of the sample were illiterate, 66.67% reduction in emergency room (p = 0.0044, odds ratio 5.33). and 60% in hospitalizations (p = 0.0023, odds ratio 7.5) in the sample (compared to the control group); INR measurements were analyzed using as the link function Quasi-Binomial: considering random effect (repeated measures of the target INR (2-3) in individuals) observed that there is a statistically significant difference in favor of the sample with p = 0.043 and odds ratio = 1.25. For fixed effects, the results, the hypothesis tested in this study demonstrates that, over time, with the frequency of INR medios within the target range, we are more likely to keep him on this track with p <0, 0001. The dispensation of a systematic and conscious of Warfarin, ensures a higher rate of maintenance of the INR target range, bringing benefits to the patient and the financial institution.